136 Early Ambulatory Blood Pressure Monitoring Post Stroke. (16th September 2019) - D'Alton, Maeve; Donaghy, Lisa; Farrell, Sarah; Hartigan, Denise; Leguis, Flordelie; Long, Shirley; McAteer, Claire; Morrison, Laura; O'Connor, Marie; Dolan, Eamon
Abstract: Background: While hypertension is the leading cause of stroke, early blood pressure (BP) management post event can be a challenge. Adjustment of antihypertensive medications is largely based on daytime ward readings. Abnormal nocturnal BP patterns may go undetected with increased risk to the patients from either extreme of BP. 24-hour ABPM has been shown to provide additional prognostic information over routine clinic measurements. We evaluated stroke patients for abnormal circadian BP profiles early after their event. Methods: Patients admitted with a stroke, whose BP had normalised for at least 48 hours, were invited to participate. ABPM was fitted for 24 hours and readings compared with routine ward BP measurements. Daytime BP was calculated between 9am-9pm; nighttime midnight-6am. Additional information was gathered on medical history, cardiovascular risks and neuroimaging. Results: Twenty-nine patients were recruited (median 6 days post event) with mean age 70.5, 62% male. The majority (86.2%) had ischaemic stroke or TIA. Seventeen had diagnosed hypertension and were taking median of 2 medications. Mean baseline ward systolic BP was 129mmHg (range 104-148 mmHg). Mean systolic BP on ABPM was 126mmHg (range 92-154 mmHg) and 123mmHg (range 93-181 mmHg) for daytime and nighttime respectively. Patients with a history of atrial fibrillation (N=13) had a higher prevalence of a non-dipping pattern, with an average 10.4 mmHg rise in their nighttime systolic BP compared with a 3mmHg fall in those without atrial fibrillation (p = 0.011). They also exhibited greater BP variability. Conclusion: In this pilot study, through the use of early ABPM we found high rates of non-dipping nocturnal BP in patients following stroke, particularly in those with underlying atrial fibrillation. The availability of 24-hour BP might allow for more individualised antihypertensive management particularly at this high-risk acute stage. Furthermore the presence of abnormal circadian patterns might be a marker for conditions such as atrial fibrillation and obstructive sleep apnoea that compound stroke risk.